To help or punish in the face of unfairness: men and women prefer mutually-beneficial strategies over punishment in a sexual selection context. Issue 9 (4th September 2019) - Ferguson, Eamonn; Quigley, Erin; Powell, Georgia; Stewart, Liam; Harrison, Freya; Tallentire, Holly
Abstract : Consistent with a sexual selection account of cooperation, based on female choice, men, in romantic contexts, in general display mutually-beneficial behaviour and women choose men who do so. This evidence is based on a two-choice - architecture (cooperate or not). Here we extend this to include punishment options using a four-choice-architecture ('punishing a transgressor', 'compensating a victim', 'both punishing and compensating' or 'doing nothing'). Both compensation (a self-serving mutually-beneficial behaviour) and self-serving punishment, are associated with positive mate qualities. We test which is preferred by males and chosen by female undergraduates. We further explore effects of trait empathy and political ideology on these preferences. In a series of three studies using a third-party punishment and compensation (3PPC) game we show (Study One), that romantically-primed undergraduate males, express a preference to either 'compensate' or 'both compensate and punish', and undergraduate women find males who 'compensate' or 'compensate and punish' the most attractive (Studies Two and Three). Compensating men are perceived as compassionate, fair and strong by undergraduate women (Study Three). High trait empathy (Studies One and Three) and a left-wing political ideology (Study Three) are associated with a preference for compensation. Thus, self-serving mutually-beneficial behaviour can be preferred over self-serving punishment as a signal of mate quality in undergraduates. Implications for the evolution of cooperation are discussed with respect to sexual selection.